2022
DOI: 10.3390/encyclopedia2010039
|View full text |Cite
|
Sign up to set email alerts
|

Smoke Hazards of Tall Timber Buildings with New Products

Abstract: Timber buildings can now stand very tall using new products. As timber materials are expected to be easily ignitable, the fire hazard of timber is a concern. Charring of the timber surface would maintain structural stability, but would also be accompanied by smoke. Although treating timber products with fire retardants would delay the ignition time under low radiative heat flux, toxic combustion products and unburnt fuel would be emitted immediately upon burning. More smoke and higher toxic gas concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…To date, the burning behavior of timber has been complex. The processes behind pyrolysis, ignition, and combustion are generally well understood [13], with good agreement in the fire science literature over a wide range of experimental conditions for crucial parameters such as critical heat flux for ignition (12 kW/m 2 ± 2 kW/m 2 ) and heat of combustion (17.5 MJ/kg ± 2.5 MJ/kg). These parameters are vital for evaluating the risks of using timber as a construction material [26].…”
Section: Timber Chemical and Physical Propertiesmentioning
confidence: 62%
See 4 more Smart Citations
“…To date, the burning behavior of timber has been complex. The processes behind pyrolysis, ignition, and combustion are generally well understood [13], with good agreement in the fire science literature over a wide range of experimental conditions for crucial parameters such as critical heat flux for ignition (12 kW/m 2 ± 2 kW/m 2 ) and heat of combustion (17.5 MJ/kg ± 2.5 MJ/kg). These parameters are vital for evaluating the risks of using timber as a construction material [26].…”
Section: Timber Chemical and Physical Propertiesmentioning
confidence: 62%
“…Conversely, softwoods, such as spruce and pine, are easily ignited due to their porous, cellular structure, and they burn faster while releasing relatively more heat [39,50]. The fire behavior of timber structures is, among other factors, dependent on the fire behavior of timber, and many related studies have been reported [13]. Understanding these disparities aids in grasping the behavior of wood under fire conditions, thereby providing a scientific foundation for fire safety design.…”
Section: Timber Chemical and Physical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations